PERFORMANCE ENGLISH TEST IN SCHOOL EXAMINATION IN INDONESIA: IS IT STUDENT`S NEED? - Leny Hikmah Rentiana (Journal of Student Research, 2023)
The purpose of this study was to investigate the performance English test in school examination in Indonesia education system through students’ perception. The school examination is a test to determine whether students can pass and continue to higher education. The goal held in the school Examination English test is a measure of success or failure of students in academic performance. research describe is closely related to the performance of 3rd graders of senior high school in performing English test in the school examination. Overall the students showed their performance in the English language test of school examination according to their intellectual ability. It consists of 15 students (4 males and 11 females) at Annida Al Islamy Junior High School who were passed school examination in 2021-2022 academic years. The participants were selected through convenient (availability) sampling procedure. This study was designed as qualitative study. In collecting the data, the writer used online questionnaire to identify students’ perception on English school examination in Indonesia education system. The findings show that the writers get some students’ perception on performance English test in school examination of school students in three aspects. They are psychologies and social domain, behaviour domain, and cognitive domain. In psychologies and social domain showed 13% the participants disagree, 54% the participants agree, and 33% the participants strongly agree that performance English test in school examination is able to measure ability in writing. There are 80% the participants also agree and 20% the participants strongly agree that performance English test in the texts of monologue such as narrative, recount, descriptive, report are very important as a student.